Mental health nursing : the working lives of paid carers in the nineteenth and twentieth centuries - Borsay, Anne; Dale, Pamela, 1975- (Nursing history and humanities., 2015)
This book seeks to integrate the history of mental health nursing with the wider history of institutional and community care. It develops new research questions by drawing together a concern with exploring the class, gender, skills and working conditions of practitioners with an assessment of the care regimes staff helped create and patients' experiences of them. Contributors from a range of disciplines use a variety of source material to examine both continuity and change in the history of care over two centuries. The book benefits from a foreword by Mick Carpenter and will appeal to research.